Ecological Perspective towards the song of Earth by Michael Jackson - Irpan Ali Rahman (e-LinguaTera, 2022)
The study aimed to know how the Ecolgical perspective in analyzing the song Earth. There are relation between humans and nature represented in the song. This study uses qualitative method to analyze the song. In the findings, the writer found that there is the disharmonic relationship between humans and nature that represented ecology matters, the next finding is the environmental imagination is revealed by the past, present and future in the song as the environmental history.